Investigating young consumer's boycott behavior in an emerging market - Dessy Kurnia Sari; Donard Games (Cogent Business & Management, 2024)
This paper evaluates young consumers' motivation in boycotting foreign products and brands in an emerging market. The study was conducted in Indonesia which is well-known for devout, religious citizens, using a mixed method. Twenty young people (aged 18–24 years old) interviewees with equal numbers of Muslims and non-Muslims were part of the initial qualitative phase. In the quantitative phase, a total of n = 383 respondents, which included 244 young Muslims and 139 young non-Muslims in Indonesia, participated in the online survey. This study compared consumers' motivation, of young Muslims and young non-Muslims, in boycotting foreign products and brands in an emerging market. The results showed that young consumers' reasons for participating in boycotts are not solely religious. Other motives included animosity, health consciousness, peer pressure, ethnocentrism, self-enhancement, and attitude. Additionally, this study evaluated the moderating effect of religiosity. The results signified that for young Muslim respondents, religiosity did not moderate the relationship between animosity, health consciousness, peer pressure, ethnocentrism, self-enhancement, attitude toward boycott as well as their intention to boycott foreign products. For young non-Muslim customers, religiosity moderates their ethnocentrism and attitude. The significant effects of young non-Muslim customers' motives to boycott foreign products were only due to ethnocentrism and attitude toward boycott. These results are useful for marketers targeting young consumers in an emerging market economy. Marketing strategies to prevent young Muslim and non-Muslim consumers from boycotting a product/brand are discussed.This paper talks about some possible reasons behind boycott behaviour of young consumers. It compares young Muslims and non-Muslim consumers' intention to boycott foreign products Indonesia. There are some important factor such as animosity, health consciousness, peer pressure, ethnocentrism, self-enhancement, and attitude. In brief, this study offers some boycott reasons that marketers should be aware of either rationality such as healthy life style or `irrational behavior' such as animosity. Social media makes the boycott calling and activities become much easier from time to time. Consequently, marketer should pay their attention to potentially viral issues in social media especially related to anger or disapproval about activities surrounding a brand because it may lead into boycott intention.
Keywords: 650; Boycott behaviour; young consumers; emerging market; indonesia; Muslim consumer behaviour